Microwave Studies on Synthesis of Some New Heterocyclic Chalcone and Pyrimidine-2-thione Derivatives and Their Antibacterial Activity - Mistry, R.N.; Desai, K.R. (Asian Journal of Chemistry, 2012)
Chalcone derivatives [1(a-j)] were prepared by condensing acetophenone with various substituted aldehydes. These chalcones react with hydrazine hydrate and glacial acetic acid to give 1-acetyl pyrazolines and in turn 1-acetyl pyrazolines react with various substituted aldehydes to give various chalcone derivatives. Pyrimidine-2-thione derivatives [2(a-j)] were prepared by condensing substituted chalcones with thiourea in presence of dil. HCl by using ethanol as a solvent. All these reactions are carried out in borosil beaker under microwave irradiation in microwave oven. These products have been characterized by means of elemental analysis and IR spectral studies and tested for antibacterial activities against S. aureus and E. coli.